Uma experiência didática com o texto argumentativo no ensino fundamental: o uso dos operadores argumentativos - Santos, Leandro Ferreira dos (2014)
This research is based on studies of Argumentative Semantics and textual linguistics. It focus on argumentation and textual organization, aiming to observe the use and advancement in the use of argumentative operators that elementary school students have done in textual productions of the genre opinion piece. The texts collected were produced at different moments. At first, the students produced freely from a controversial topic that was selected by themselves. At the second stage of this observation, the students produced texts under supervision, this activity aimed to contribute to a more efficient use of argumentative operators and, therefore, we base our study in the use of didactic sequence proposed by Dolz, Schneuwly and Noverraz (2010). The theoretical background is based on the authors Ducrot (1987.1988), Garcia (2010), Marcuschi (2008), Koch (2000.2011), Birth (2012) and Cabral (2011). The argument will be treated from the studies developed by French Oswald Ducrot. The TAL (Argumentation Theory in Language) is based on the notion that argumentativity is inserted in the linguistic form. The work presented is the result of a search action, considering that I am a teacher of students whose writings formed the corpus for analysis, as well as being the researcher. During the collection of the corpus, the analyze was developed taking into account the socionteracionist theory of language, which takes into consideration the context that involves the written practice, that is, a process which involves the writer, the purpose of the material written, and the interaction with the receiver. This study is the outcome of a particular research, considering that I am the teacher of the students who provided the corpus for this analysis, as well as I am the researcher. While analyzing the texts, we followed the qualitative procedures. At first, we tried to identify the occurrence of argumentative operators in two versions of the genre investigated and its diversities of forms, aiming to quantify both operators and forms. In a second moment, this analyze focused on the use of these operators aiming to see if the use thereof has reached the communicative purpose desired. Thus, in this analyze, it was possible to verify whether there was adequate textual articulation in a sense of effective appropriation and use of these operators, and also if the discursive relations established were architected in better argumentative way.